Antonio Muñoz Molina, Carlota Fainberg, Madrid: Alfaguara, 1999, 174 p. - Corbellini, Natalia (2000)
Fil: Corbellini, Natalia. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.